THE IMPLEMENTATION OF DIGITAL-BASED READING COMPREHENSION TEST TO STUDENTS : A LIBRARY RESEARCH - Theodora Evita Bella Lumban Raja; Rika Budiarti; Cinta Yulistra Tindaon; Pika Marselli Simarmata; Marino Sihombing (Jurnal Intelek Insan Cendikia, 2025)
This research delves into the implementation of digital-based reading comprehension test within educational environments, highlighting both its effectiveness and the challenges it presents. As digital learning tools become increasingly woven into educational curricula, this research investigates how technology can enrich the evaluation of reading comprehension. In a comprehensive exploration of pertinent literature, researchers analyzed the benefits and challenges associated with the implementation of digital-based reading comprehension test. Our key findings indicate that digital tests provide numerous benefits, including immediate feedback, adaptability, and enhanced accessibility, all of which significantly bolster students engagement and learning outcomes. Nonetheless, this research also addresses several challenges, such as technological constraints, gaps in digital literacy, and the necessity for well-structured test frameworks. This research culminates in a series of insightful recommendations aimed at educators and policymakers, advocating for integration of digital tests to enhance the development of reading comprehension skills among students.